2022
DOI: 10.7326/m21-2452
|View full text |Cite
|
Sign up to set email alerts
|

Association of AZD1222 and BNT162b2 COVID-19 Vaccination With Thromboembolic and Thrombocytopenic Events in Frontline Personnel

Abstract: Case reports of thrombotic adverse events after vaccination with the Oxford–AstraZeneca COVID-19 vaccine have raised concerns. This retrospective cohort study evaluated the risk for thromboembolic and thrombocytopenia-related events after COVID-19 vaccination with the Oxford–AstraZeneca and Pfizer–BioNTech vaccines in a nationwide cohort of 365 353 Danish frontline personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…As both Danish studies used the same database, differences in endpoint (all-cause vs. cardiac mortality) or study design (self-controlled vs. matched control) may explain their discrepant findings. Hviid et al [ 29 ] further speculated that the infrequent administration of COVID-19 vaccines to terminally ill patients might contribute to the lower mortality rate in BNT162b2 recipients in their study.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As both Danish studies used the same database, differences in endpoint (all-cause vs. cardiac mortality) or study design (self-controlled vs. matched control) may explain their discrepant findings. Hviid et al [ 29 ] further speculated that the infrequent administration of COVID-19 vaccines to terminally ill patients might contribute to the lower mortality rate in BNT162b2 recipients in their study.…”
Section: Resultsmentioning
confidence: 89%
“…Mortality is another reliable indicator of vaccine safety since it captures nearly all aspects of fatal adverse events regardless of disease types. One study from Denmark found no significant differences in death rates between BNT162b2-vaccinated and unvaccinated individuals [ 29 ]. However, another Danish study reported a 49% decreased risk of cardiac arrest or death in BNT162b2 recipients compared to non-recipients [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Another retrospective cohort study in Denmark did not identify statistically significant risk difference of thromboembolic events between vaccinated with BNT162b2 and unvaccinated people. 8 A SCCS study conducted in the United Kingdom showed an increased risk of thromboembolism after first dose of both Vaxzevria and BNT162b2 vaccine. 9 Other case reports of thrombosis or hemorrhage in the brain or leg were reported with Pfizer-BioNTech covid-19 mRNA vaccine (BNT162b2).…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) following the Pfizer BioNTech mRNA COVID vaccine appears to be a rarely reported complication, and a recent retrospective cohort study of Danish frontline personnel who received priority COVID-19 vaccination showed no statistically significant association of the Pfizer BioNTech mRNA COVID vaccine with thrombotic or thrombocytopenic events [2]. Amongst the Danish population, approximately 6% are heterozygous for the FVL G169A mutation [3] and the frequency of homozygosity for the A1298C variant of the MTHFR gene is expected to be about 14.6%, based on data from a Scottish population [4].…”
Section: Dear Editormentioning
confidence: 99%